Increasing Kindergarten Children's Creativity By Utilizing Trash and Used Goods as Learning Media - Dian Yuli Kuswati; Rahmat Mulyono (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
Motivated by the problem of the large amount of waste around Mutiara Bunda Kindergarten and especially the location of the Mutiara Bunda Kindergarten school adjacent to the landfill where there is plastic waste such as used cardboard bottles that are no longer used, there is a need for solutions in dealing with waste or inorganic plastic waste and so on. The purpose of this study is to increase the use value of waste or used goods to increase the creativity of students from Mutiara Bunda Baleharjo Wonosari Kindergarten, Gunung Kidul. The research method is carried out through the observation stage of the implementation location and in direct collaboration with the landfill, conceptual activities conditioning participants in this case are children of Mutiara Bunda Kindergarten in increasing children's creativity, coordination with related parties waste managers, collaborating with accompanying teachers, guardians / parents, school committees followed by preparation materials and tools, integrated with the school curriculum, evaluation of plans and follow-up. The real result of this activity is an increase in the use value of waste or used goods so that it can also reduce waste in the school environment of Mutiara Bunda Kindergarten, another purpose is to use used goods as a medium for increasing children's ideas, creations and innovations in increasing children's creativity in learning and playing activities. With the use of waste and used goods as a learning medium, it will help the effectiveness of the learning process and the delivery of messages and learning content. Learning media is useful in clarifying teaching materials, overcoming time and space, encouraging children to be more active, and can increase cooperation. And with the benefits of using a learning media will be optimally felt if the teacher is able to choose and use the learning media in accordance with its purpose and function.